The Cold War from the Margins : A Small Socialist State on the Global Cultural Scene - Dragostinova, Theodora 1972- (Cornell University Press, 2021)
"Interprets the global dynamics of the late Cold War in the 1970s from the perspective of a small state, Bulgaria, and its cultural diplomacy in the Balkans, the West, and the Third World" Provided by publisher